Pengaruh Hypnobreastfeeding Terhadap Kelancaran Pengeluaran ASI Pada Ibu Nifas Di PMB Soraya Palembang - Devina Anggrainy Dencik (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Babies get their main nutrition, namely breast milk, through the breastfeeding process. However, in some cases breast milk can be low, one of the reasons is the mother's psychological condition. Mothers who feel unhappy, not calm, not relaxed, this will affect their breast milk. Hypnobreastfeeding is a relaxation technique to help smooth the breastfeeding process, by adding positive affirmations to your mind when you relax. Deep and regular relaxation makes the endocrine system, blood flow and other systems in the body function better because the endorphins produced by the mother will flow to the baby through breast milk and also make the baby feel comfortable and calm. Research objective: to determine the effect of hypnobreastfeeding on the smooth flow of breast milk in postpartum mothers at PMB Soraya Palembang. Method: This research uses a pre-experimental research design (one-group pre-post test design). The sampling technique used was total sampling with a total of 32 people. Univariate data analysis for homogeneity and bivariate tests used the dependent t test. The results of this study showed that respondents experienced an increase in breast milk production obtained from the pretest and posttest. The results of the dependent t test obtained a Z value of -2.129 and Asymp Sig of 0.001 < 0.005. The conclusion of this research states that there is an influence of the hypnobreastfeeding technique in expressing breast milk to the mother